2017
DOI: 10.1111/idj.12317
|View full text |Cite
|
Sign up to set email alerts
|

The association between oral hygiene and periodontitis: a systematic review and meta-analysis

Abstract: ObjectiveDental plaque accumulation and inadequate personal oral hygiene (OH) are known major risk factors of periodontitis. Nevertheless, the magnitude of their effects has not yet been the subject of a meta‐analysis.Material and methodsThe Medline and Scopus databases were searched up to May 2016. Observational studies were eligible if they assessed associations between OH and periodontitis in adult subjects. A multivariate random‐effects meta‐analysis was used to pool the effects of fair/poor OH versus good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
196
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(231 citation statements)
references
References 75 publications
22
196
0
13
Order By: Relevance
“…The dysbiotic bacterial biofilm (dental plaque and root calculus) was associated with increasing the risk of deterioration of periodontal health in this cohort of adolescents. This finding is in agreement with and further extends the systematic review by Lertpimonchai et al . who concluded that fair to poor oral hygiene is a risk factor for periodontitis in adults.…”
Section: Discussionsupporting
confidence: 93%
“…The dysbiotic bacterial biofilm (dental plaque and root calculus) was associated with increasing the risk of deterioration of periodontal health in this cohort of adolescents. This finding is in agreement with and further extends the systematic review by Lertpimonchai et al . who concluded that fair to poor oral hygiene is a risk factor for periodontitis in adults.…”
Section: Discussionsupporting
confidence: 93%
“…The most logical explanation for this is poor oral hygiene. Studies have shown that poor oral hygiene is a classical risk factor of periodontitis as well as peri‐implantitis . In the present study nearly 72% individuals in group‐2 reported to brush their teeth once daily and none of the individuals in either group reported to have ever used a dental floss.…”
Section: Discussionmentioning
confidence: 39%
“…28 Furthermore, nornicotine (a metabolite of nicotine), upregulates the expression of RAGE in the gingival tissues of smokers and stimulates the formation reactive oxygen species, which jeopardize the oral soft tissues and increases bone loss around teeth. 26 Studies have shown that poor oral hygiene is a classical risk factor of periodontitis 34,35 as well as peri-implantitis. 36,37 In the present study nearly 72% individuals in group-2 reported to brush their teeth once daily and none of the individuals in either group reported to have ever used a dental floss.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have shown that oral hygiene status affects periodontal condition, poor oral hygiene in RA patients may lead to periodontitis. In a previous case‐control study comparing RA patients and control subjects matched for age, sex, smoking status, and oral hygiene status, the RA patients had greater gingival inflammation and chronic periodontal destruction, and more missing teeth, compared with the controls .…”
Section: Discussionmentioning
confidence: 94%